General Structures of Block Based Interpolational Function (Communications in Mathematical Research, 2021)
We construct general structures of one and two variable interpolationfunction, without depending on the existence of divided difference or inverse differences, and we also discuss the block based osculatory interpolation in one variablecase. Clearly, our method offers many flexible interpolation schemes for choices. Error terms for the interpolation are determined and numerical examples are given toshow the effectiveness of the results.